Evolving etiologies of liver transplantation: a trend analysis from 2020 to 2024 at the main center of Iran - Jamalinia, Mohamad; Bagheri Lankarani, Kamran; Malek-Hosseini, Seyed Ali (Gastroenterology and hepatology from bed to bench, 2025)
This study aimed to analyze trends in the etiologies of liver transplants at Abu Ali Sina Hospital, Shiraz, Iran, from 2020 to 2024. Liver transplantation (LT) is a crucial treatment for end-stage liver disease (ESLD). Over time, the etiologies leading to LT have evolved due to changes in disease prevalence, advancements in medical treatments, and public health interventions. Etiologies of LT were categorized into nine groups: acute liver failure, autoimmune disorders, alcoholic steatohepatitis, liver cancer, vascular, metabolic dysfunction-associated steatohepatitis (MASH), viral hepatitis, metabolic disorders, and others. Trend analysis was performed using Python 3.12 programming language with appropriate libraries. A total of 1579 patients, 59.9% male with a mean age of 45.12 years (SD: 13.52), were analyzed. Autoimmune disorders emerged as the leading cause of LT, increasing from 32.2% in 2020 to 40.6% in 2024 (p-trend = 0.039). Viral hepatitis cases decreased significantly from 18.1% to 3.0% (p-trend = 0.033). Liver cancer became the third leading cause in 2021, replacing viral hepatitis, while MASH consistently remained the second leading cause. The significant shifts in LT etiologies underscore the success of public health interventions in reducing the burden of viral-related ESLD. Additionally, the findings highlight the need for ongoing research into the prevention, early diagnosis, and management of autoimmune liver diseases, MASH, and liver cancer. These findings provide critical insights for clinicians and policymakers to enhance liver disease management and allocate resources effectively.